Rolled copper foil preparation method and rolled copper foil
By adding Sn and P elements to the copper solution and combining reasonable processing and surface treatment processes, the problem of poor folding resistance of the rolled copper foil is solved, and the effect of significantly improving the bending resistance and oxidation resistance is achieved.
Patent Information
- Application Number
- CN202411655282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing rolled copper foils are prone to fracture and cracks during bending and folding operations, resulting in poor folding resistance and affecting product quality and service life.
Sn and P elements were added during the smelting process of copper solution, and the Sn content was controlled to be 0.10-0.12 wt%, and the P content was 0.01-0.05 wt%. Through reasonable processing technology and surface treatment technology, the mechanical properties of copper foil were improved and Antioxidant properties.
Through the addition of Sn and P elements and the optimization of processing technology, the bending resistance of the rolled copper foil is significantly improved, with the number of folding resistance up to 639 times, while maintaining good conductivity and oxidation resistance.
Smart Images

Figure CN119464795A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil, and in particular to a method for preparing a rolled copper foil and the rolled copper foil. Background Art
[0002] With the rapid development of electronic equipment, it is gradually developing towards lightness, thinness and speed. As an indispensable basic material for the production of printed circuit boards (PCBs), copper clad laminates (FCCLs) and lithium-ion batteries, the demand for rolled copper foil in aerospace equipment, aircraft instruments, mobile phones, military equipment and daily electronic equipment is increasing. Rolled copper foil has excellent anti-oxidation properties based on its good ductility, bending resistance, conductivity, etc., and various surface treatment technologies are carried out on this basis. However, with the continuous development of related industries, higher requirements are put forward for copper foil.
[0003] Especially in terms of the folding resistance of copper foil, due to its own physical properties and the limitations of the preparation process, copper foil is prone to breakage and cracks during bending and folding, which seriously affects the quality and service life of the product. Therefore, developing a preparation process that can significantly improve the folding resistance of copper foil is of great significance to improving the overall level of the electronics industry. Summary of the invention
[0004] In view of the above problems, the present invention is proposed to provide a method for preparing a rolled copper foil and a rolled copper foil that overcome the above problems or at least partially solve the above problems, and can solve the problem of poor folding resistance of existing rolled copper foil.
[0005] Specifically, the present invention provides a method for preparing a rolled copper foil, comprising the following steps:
[0006] Smelting: Sn and P elements are added to the copper solution during the smelting process. After the smelting is completed, the Sn content in the solution is 0.10-0.12wt%, and the P content is 0.01-0.05wt%.
[0007] Optionally, in the smelting step, the solution after smelting further contains the following components:
[0008] Cu+Ag≥99.85wt%;
[0009] S≤0.0015wt%;
[0010] Fe≤0.001wt%;
[0011] Zn≤0.0001wt%;
[0012] Bi≤0.0001wt%;
[0013] Sb≤0.0004wt%;
[0014] Ni≤0.001wt%;
[0015] Pb≤0.0005wt%;
[0016] O≤0.0005wt%.
[0017] Optionally, the content of Sn is 0.11-0.12 wt %; and / or
[0018] The content of P is 0.031 to 0.05 wt%.
[0019] Optionally, after the smelting step, the method for preparing the rolled copper foil further comprises the following steps in sequence: casting, hot rolling, milling, rough rolling, intermediate rolling, finish rolling, and foil rolling.
[0020] Optionally, in the casting step: a semi-continuous casting method is used, the casting temperature is controlled to be 900° C. to 1100° C., and the temperature is kept at 900° C. to 1100° C. for 2 hours, and an ingot is obtained after the casting is completed.
[0021] Optionally, in the hot rolling step: the starting rolling temperature is 850° C., the final rolling temperature is not less than 500° C., and after rolling for multiple passes, a slab with a thickness of 20 mm is obtained; and / or
[0022] In the milling step: the slab obtained in the hot rolling step is subjected to milling treatment to obtain a slab with a thickness of 16.0 mm; and / or
[0023] In the rough rolling step: rolling the slab obtained in the milling step into a strip with a thickness of 1.0 mm in multiple passes; and / or
[0024] In the intermediate rolling step: the strip obtained in the rough rolling step is annealed and then rolled into a strip with a thickness of 0.4 mm in two passes; and / or
[0025] In the finishing rolling step: the strip obtained in the intermediate rolling step is subjected to continuous annealing treatment and then rolled into a copper strip with a thickness of 0.15 mm; and / or
[0026] In the foil rolling step: the copper sheet strip obtained in the finish rolling step is subjected to foil rolling, which is divided into 5 to 7 rolling passes.
[0027] Optionally, in the foil rolling step, there are 6 rolling passes as follows:
[0028] First pass: entry thickness is 0.150mm, exit thickness is 0.097mm, reduction rate is 35.3%, total entry tension is 3500N, total exit tension is 5500N, rolling force is 450KN, and rolling speed is 500m / min;
[0029] Second pass: the entry thickness is 0.097mm, the exit thickness is 0.066mm, the reduction rate is 31.9%, the total entry tension is 3100N, the total exit tension is 4100N, the rolling force is 450KN, and the rolling speed is 500m / min;
[0030] The third pass: the entry thickness is 0.066mm, the exit thickness is 0.045mm, the reduction rate is 31.8%, the total entry tension is 2600N, the total exit tension is 3200N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0031] Fourth pass: the entry thickness is 0.045mm, the exit thickness is 0.032mm, the reduction rate is 28.9%, the total entry tension is 1700N, the total exit tension is 2100N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0032] The fifth pass: the entry thickness is 0.032mm, the exit thickness is 0.023mm, the reduction rate is 28.1%, the total entry tension is 1000N, the total exit tension is 1200N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0033] The sixth pass: the entry thickness is 0.023mm, the exit thickness is 0.018mm, the reduction rate is 21.7%, the total entry tension is 800N, the total exit tension is 950N, the rolling force is 450KN, the rolling speed is 650m / min, and finally a rolled copper foil with a thickness of 0.018mm is obtained.
[0034] Optionally, after the foil rolling step, the method for preparing the rolled copper foil further comprises the following steps:
[0035] Electroplating: The surface of the rolled copper foil is electroplated.
[0036] Optionally, the electroplating step comprises:
[0037] Roughening treatment: Cu in the roughening solution 2+ The ion concentration is 40g / L, the H2SO4 concentration is 120g / L, and the current density is 55A / dm 2 ;
[0038] Curing treatment: Cu in the curing liquid 2+ The ion concentration is 50g / L, the H2SO4 concentration is 80g / L, and the current density is 45A / dm 2 ;
[0039] Surface zinc plating treatment: ZnCl2 concentration in the plating solution is 50g / L, KCl concentration is 150g / L, boric acid concentration is 25g / L, the plating solution pH is 5, and the current density is 3A / dm 2 .
[0040] On the other hand, the present invention also provides a rolled copper foil produced by any of the above-mentioned methods for producing rolled copper foil.
[0041] In the present invention, a certain amount of Sn and P elements are added to the copper solution during the smelting process of the blank, so that the solution contains 0.10-0.12wt% Sn and 0.01-0.05wt% P. The Sn element can cause lattice distortion through solid solution strengthening, increase the resistance to dislocation movement, improve the strength and toughness of the rolled copper foil, and enable it to absorb more energy during the bending process, thereby effectively improving the folding resistance of the copper foil. The P element can refine the grains, reduce the grain size of the rolled copper foil, increase the grain boundary area, and hinder the movement of dislocations to the grain boundaries during bending, which can disperse stress, reduce crack generation, and improve folding resistance. Therefore, the present invention can improve the bending resistance of the rolled copper foil.
[0042] Furthermore, the present invention can further improve the bending resistance of the copper foil through a reasonable processing technology.
[0043] Furthermore, the present invention can improve the anti-oxidation performance of the copper foil through a reasonable surface treatment process.
[0044] Furthermore, the rolled copper foil product prepared by the present invention can withstand bending times of up to 639 times.
[0045] Based on the following detailed description of specific embodiments of the present invention in conjunction with the accompanying drawings, those skilled in the art will become more aware of the above and other objects, advantages and features of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:
[0047] Figure 1 It is a schematic flow chart of the method for preparing rolled copper foil in Example 1. DETAILED DESCRIPTION
[0048] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0049] The embodiment of the present invention provides a method for preparing a rolled copper foil, comprising a smelting step, wherein Sn and P elements are added in the smelting step, and after the smelting is completed, the content of Sn in the solution is 0.10-0.12wt%, and the content of P is 0.01-0.05wt%.
[0050] Specifically, after the smelting step, the method for preparing the rolled copper foil also includes the steps of casting and machining. wt% is a unit of weight percentage, which is used to indicate the mass proportion of a substance in a mixture. After the smelting is completed, the Sn content in the solution can be any one of 0.10wt%, 0.105wt%, 0.11wt%, 0.115wt%, and 0.12wt%, and the P content can be any one of 0.01wt%, 0.02wt%, 0.025wt%, 0.028wt%, 0.03wt%, 0.031wt%, 0.035wt%, 0.04wt%, 0.045wt%, 0.048wt%, and 0.05wt%.
[0051] In this embodiment, on the one hand, the Sn element can cause lattice distortion through solid solution strengthening, increase the resistance to dislocation movement, improve the strength and toughness of the rolled copper foil, and enable it to absorb more energy during the bending process, thereby effectively improving the folding resistance of the copper foil. On the other hand, the P element can refine the grains, reduce the grain size of the rolled copper foil, increase the grain boundary area, and hinder the movement of dislocations to the grain boundaries during bending, which can disperse stress, reduce crack generation, and improve folding resistance. Therefore, in this embodiment, during the smelting process of the blank, a certain amount of Sn and P elements are added to the copper solution so that the solution contains 0.10-0.12wt% Sn and 0.01-0.05wt% P, which can improve the bending resistance of the rolled copper foil.
[0052] In some optional embodiments of the present invention, in the smelting step, the solution also contains the following components after the smelting is completed: Cu+Ag≥99.85wt%; S≤0.0015wt%; Fe≤0.001wt%; Zn≤0.0001wt%; Bi≤0.0001wt%; Sb≤0.0004wt%; Ni≤0.001wt%; Pb≤0.0005wt%; O≤0.0005wt%.
[0053] Specifically, after the smelting is completed, the Cu+Ag content in the solution can be any one of 99.855wt%, 99.86wt%, 99.87wt%, and 99.88wt%.
[0054] After smelting is completed, the S content in the solution can be any one of 0.0015wt%, 0.0014wt%, 0.0013wt%, 0.0012wt%, 0.0011wt%, 0.001wt%, 0.0009wt%, 0.0005wt%, and 0.0001wt%.
[0055] After smelting is completed, the Fe content in the solution can be any one of 0.001wt%, 0.0009wt%, 0.0008wt%, 0.0007wt%, 0.0005wt%, 0.0004wt%, 0.0003wt%, and 0.0001wt%.
[0056] After smelting is completed, the Zn content in the solution can be any one of 0.0001wt%, 0.00009wt%, 0.00008wt%, 0.00007wt%, 0.00005wt%, 0.00004wt%, 0.00003wt%, and 0.00001wt%.
[0057] After smelting is completed, the Bi content in the solution can be any one of 0.0001wt%, 0.00009wt%, 0.00008wt%, 0.00007wt%, 0.00005wt%, 0.00004wt%, 0.00003wt%, and 0.00001wt%.
[0058] After the smelting is completed, the Sb content in the solution can be any one of 0.0004wt%, 0.0003wt%, 0.0002wt%, and 0.0001wt%.
[0059] After smelting is completed, the Ni content in the solution can be any one of 0.001wt%, 0.0009wt%, 0.0008wt%, 0.0007wt%, 0.0006wt%, 0.0005wt%, 0.0003wt%, and 0.0001wt%.
[0060] After the smelting is completed, the Pb content in the solution can be any one of 0.0005wt%, 0.0004wt%, 0.0003wt%, 0.0002wt%, 0.0001wt%, 0.00009wt%, and 0.00001wt%.
[0061] After the smelting is completed, the O content in the solution can be any one of 0.0005wt%, 0.0004wt%, 0.0003wt%, 0.0002wt%, 0.0001wt%, 0.00009wt%, and 0.00001wt%.
[0062] In this embodiment, since the solution after smelting is a copper alloy solution, the rolled copper foil finally prepared is a copper alloy copper foil, which has the characteristics of high strength, high hardness and strong ductility. In addition, the content of impurity elements in the solution after smelting is low, so the content of the rolled copper foil finally prepared is also relatively low, which is conducive to further improving the alloy performance, enhancing the mechanical properties and reducing the tendency of hot cracking. In summary, this embodiment is conducive to further improving the bending resistance of the rolled copper foil.
[0063] In some optional embodiments of the present invention, the content of Sn is 0.11-0.12 wt %.
[0064] In some optional embodiments of the present invention, the content of P is 0.031-0.05 wt %.
[0065] In some optional embodiments of the present invention, after the smelting step, the method for preparing the rolled copper foil further comprises the following steps in sequence: casting, hot rolling, milling, rough rolling, intermediate rolling, finish rolling, and foil rolling.
[0066] Specifically, the copper alloy solution is processed into an ingot by casting, the ingot is processed into a slab by hot rolling, the thickness of the slab is reduced by milling, the slab is processed into a strip by rough rolling, the thickness of the strip is reduced by intermediate rolling and finishing rolling, and the strip is processed into copper foil by foil rolling. Through the above processing steps, the mechanical properties of the rolled copper foil can be improved, so that it has good bending resistance.
[0067] In some optional embodiments of the present invention, in the casting step: a semi-continuous casting method is used, the casting temperature is controlled to be 900°C ~ 1100°C (for example: 900°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C), and the temperature is kept for 2 hours to obtain an ingot after the casting is completed.
[0068] In some optional embodiments of the present invention, in the hot rolling step: the starting rolling temperature is 850° C., the final rolling temperature is not less than 500° C., and after rolling for multiple passes, a slab with a thickness of 20 mm is obtained.
[0069] In some optional embodiments of the present invention, in the milling step: the slab obtained in the hot rolling step is subjected to milling treatment to obtain a slab with a thickness of 16.0 mm.
[0070] In some optional embodiments of the present invention, in the rough rolling step: the slab obtained in the milling step is rolled into a 1.0 mm thick strip in multiple passes.
[0071] In some optional embodiments of the present invention, in the intermediate rolling step: the strip obtained in the rough rolling step is annealed and then rolled into a 0.4 mm thick strip in two passes.
[0072] In some optional embodiments of the present invention, in the finish rolling step: the strip obtained in the intermediate rolling step is subjected to continuous annealing treatment and then rolled into a copper plate strip with a thickness of 0.15 mm.
[0073] In some optional embodiments of the present invention, in the foil rolling step: the copper strip obtained in the finish rolling step is subjected to foil rolling, which is divided into 5 to 7 rolling passes.
[0074] In some optional embodiments of the present invention, in the foil rolling step, there are 6 rolling passes as follows:
[0075] First pass: entry thickness is 0.150mm, exit thickness is 0.097mm, reduction rate is 35.3%, total entry tension is 3500N, total exit tension is 5500N, rolling force is 450KN, and rolling speed is 500m / min;
[0076] Second pass: the entry thickness is 0.097mm, the exit thickness is 0.066mm, the reduction rate is 31.9%, the total entry tension is 3100N, the total exit tension is 4100N, the rolling force is 450KN, and the rolling speed is 500m / min;
[0077] The third pass: the entry thickness is 0.066mm, the exit thickness is 0.045mm, the reduction rate is 31.8%, the total entry tension is 2600N, the total exit tension is 3200N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0078] Fourth pass: the entry thickness is 0.045mm, the exit thickness is 0.032mm, the reduction rate is 28.9%, the total entry tension is 1700N, the total exit tension is 2100N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0079] The fifth pass: the entry thickness is 0.032mm, the exit thickness is 0.023mm, the reduction rate is 28.1%, the total entry tension is 1000N, the total exit tension is 1200N, the rolling force is 450KN, and the rolling speed is 650m / min;
[0080] The sixth pass: the entry thickness is 0.023mm, the exit thickness is 0.018mm, the reduction rate is 21.7%, the total entry tension is 800N, the total exit tension is 950N, the rolling force is 450KN, the rolling speed is 650m / min, and finally a rolled copper foil with a thickness of 0.018mm is obtained.
[0081] In some optional embodiments of the present invention, after the foil rolling step, the method for preparing the rolled copper foil further includes an electroplating step of electroplating the surface of the rolled copper foil.
[0082] Through the electroplating process, an electroplating layer can be formed on the surface of the rolled copper foil, so that the rolled copper foil can have good anti-oxidation properties.
[0083] In some optional embodiments of the present invention, the electroplating step includes: roughening treatment, curing treatment and surface galvanizing treatment.
[0084] Furthermore, before the roughening step, a pretreatment step is also included to clean the surface of the rolled copper foil to improve the flatness of the electroplated coating. The pretreatment step includes processes such as degreasing and pickling.
[0085] In some optional embodiments of the present invention, in the roughening step: Cu in the roughening solution 2+ The ion concentration is 40g / L, the H2SO4 concentration is 120g / L, and the current density is 55A / dm 2 .
[0086] In some optional embodiments of the present invention, in the curing step: Cu in the curing liquid 2+ The ion concentration is 50g / L, the H2SO4 concentration is 80g / L, and the current density is 45A / dm 2 .
[0087] In some optional embodiments of the present invention, in the surface zinc plating treatment step: the ZnCl2 concentration in the plating solution is 50g / L, the KCl concentration is 150g / L, the boric acid concentration is 25g / L, the plating solution pH is 5, and the current density is 3A / dm 2 .
[0088] An embodiment of the present invention further provides a rolled copper foil, which is a rolled copper foil prepared by the method for preparing the rolled copper foil of any one of the above embodiments.
[0089] The implementation scheme of the present application will be described in detail below with reference to specific examples.
[0090] Example 1
[0091] like Figure 1 As shown, a method for preparing a rolled copper foil comprises the following steps:
[0092] (1) Smelting: Sn and P elements are added to the copper solution during the smelting process. After the smelting is completed, the solution contains the following components: Cu+Ag≥99.85wt%, S≤0.0015wt%, Fe≤0.001wt%, Zn≤0.0001wt%, Sn: 0.10-0.12wt%, Bi≤0.0001wt%, Sb≤0.0004wt%, Ni≤0.001wt%, Pb≤0.0005wt%, O≤0.0005wt%, P: 0.01-0.05wt%.
[0093] (2) Casting: A semi-continuous casting method is used, the casting temperature is controlled at 900°C to 1100°C, and the temperature is kept at this temperature for 2 hours. After the casting is completed, an ingot is obtained.
[0094] (3) Hot rolling: The starting rolling temperature is 850°C, and the final rolling temperature is not less than 500°C. After rolling for multiple passes, a slab with a thickness of 20 mm is obtained.
[0095] (4) Milling: After the 20 mm thick slab is milled, a 16.0 mm thick slab is obtained.
[0096] (5) Rough rolling: The 16.0 mm thick slab is rolled into 1.0 mm thick strip in multiple passes.
[0097] (6) Intermediate rolling: After annealing, the 1.0 mm thick strip is rolled into a 0.4 mm thick strip in two passes.
[0098] (7) Finish rolling: After continuous annealing, the 0.4 mm thick strip is rolled into a copper plate with a thickness of 0.15 mm.
[0099] (8) Foil rolling: The copper strip is subjected to foil rolling, which is divided into 6 rolling passes.
[0100] First pass: entry thickness is 0.150mm, exit thickness is 0.097mm, reduction rate is 35.3%, total entry tension is 3500N, total exit tension is 5500N, rolling force is 450KN, and rolling speed is 500m / min.
[0101] The second pass: the entry thickness is 0.097mm, the exit thickness is 0.066mm, the reduction rate is 31.9%, the total entry tension is 3100N, the total exit tension is 4100N, the rolling force is 450KN, and the rolling speed is 500m / min.
[0102] The third pass: the entry thickness is 0.066mm, the exit thickness is 0.045mm, the reduction rate is 31.8%, the total entry tension is 2600N, the total exit tension is 3200N, the rolling force is 450KN, and the rolling speed is 650m / min.
[0103] The fourth pass: the entry thickness is 0.045mm, the exit thickness is 0.032mm, the reduction rate is 28.9%, the total entry tension is 1700N, the total exit tension is 2100N, the rolling force is 450KN, and the rolling speed is 650m / min.
[0104] The fifth pass: the entry thickness is 0.032mm, the exit thickness is 0.023mm, the reduction rate is 28.1%, the total entry tension is 1000N, the total exit tension is 1200N, the rolling force is 450KN, and the rolling speed is 650m / min.
[0105] The sixth pass: the entry thickness is 0.023mm, the exit thickness is 0.018mm, the reduction rate is 21.7%, the total entry tension is 800N, the total exit tension is 950N, the rolling force is 450KN, the rolling speed is 650m / min, and finally a rolled copper foil with a thickness of 0.018mm is obtained.
[0106] (9) Electroplating treatment: The surface of the rolled copper foil is electroplated to form a protective film on the surface of the rolled copper foil.
[0107] The electroplating process includes the following steps:
[0108] Roughening treatment: Cu in the roughening solution 2+ The ion concentration is 40g / L, the H2SO4 concentration is 120g / L, and the current density is 55A / dm 2 .
[0109] Curing treatment: Cu in the curing liquid 2+ The ion concentration is 50g / L, the H2SO4 concentration is 80g / L, and the current density is 45A / dm 2 .
[0110] Surface zinc plating treatment: ZnCl2 concentration in the plating solution is 50g / L, KCl concentration is 150g / L, boric acid concentration is 25g / L, the plating solution pH is 5, and the current density is 3A / dm 2 .
[0111] (10) Cooling and drying: The electroplated rolled copper foil is cooled and then dried to obtain the final rolled copper foil product.
[0112] The performance of the rolled copper foil product prepared in this embodiment was tested:
[0113] (1) Copper foil folding performance test
[0114] The MIT folding strength test machine was used to conduct the MIT folding resistance test, which used a weight of 500g, a bending radius of R=0.8mm, and a bending angle of 135°. According to the test, the folding resistance of the rolled copper foil product can reach 639 times. It can be seen that the present invention can effectively improve the folding resistance of the copper foil.
[0115] (2) Other performance tests
[0116] The rolled copper foil product maintains more than 90% IACS of the international annealed copper conductivity standard, and the strength reaches 550MPa. In an environment of 5% NaCl and 35°C, the rolled copper foil product does not corrode for 24 hours. It can be seen that the rolled copper foil of this embodiment has good comprehensive physical properties.
[0117] In summary, this embodiment provides a preparation process for improving the folding resistance of copper foil. This embodiment can greatly improve the bending resistance of copper foil by adding a certain amount of Sn and P elements during the smelting process of the blank, and then undergoing reasonable processing technology and surface treatment technology. Among them, the Sn element will cause lattice distortion through solid solution strengthening, increase the resistance to dislocation movement, improve the strength and toughness of the copper foil, and enable it to absorb more energy during the bending process, thereby effectively improving the folding resistance of the copper foil; the P element can refine the grains, reduce the grain size of the copper foil, increase the grain boundary area, and hinder the movement of dislocations to the grain boundaries during bending, which can disperse stress, reduce crack generation, and improve folding resistance. In addition, surface electroplating treatment can make the rolled copper foil have better anti-oxidation properties. Thereby, a rolled copper foil with good comprehensive performance is finally obtained.
[0118] Comparative Example 1
[0119] The method for preparing the rolled copper foil comprises the following steps:
[0120] (1) Smelting: During the smelting process, a certain amount of O element is added to control the O content to 100-230 ppm to obtain an oxygen-containing copper billet.
[0121] (2) Casting: A semi-continuous casting method is used, the casting temperature is controlled at 800°C to 1000°C, and the temperature is kept at this temperature for 2 hours. After the casting is completed, an ingot is obtained.
[0122] (3) Hot rolling: The starting rolling temperature is 800°C, and the final rolling temperature is not less than 450°C. After rolling for multiple passes, a slab with a thickness of 20 mm is obtained.
[0123] (4) Milling: After milling the 20.0 mm slab, a 16.0 mm thick slab is obtained.
[0124] (5) Rough rolling: The 16.0 mm thick slab is rolled into 1.0 mm thick strip in multiple passes.
[0125] (6) Intermediate rolling: After annealing, the 1.0 mm strip is rolled into a 0.4 mm thick strip in two passes.
[0126] (6) Finish rolling: The 0.4 mm thick strip is continuously annealed and then rolled into a copper strip with a thickness of 0.15 mm.
[0127] (8) Foil rolling: After intermediate annealing, the copper strip is subjected to foil rolling to further reduce the thickness of the copper foil. The foil rolling process includes the following steps:
[0128] The first pass has an entry thickness of 0.150 mm, an exit thickness of 0.097 mm, a reduction rate of 35.3%, a total entry tension of 3500 N, a total exit tension of 5500 N, a rolling force of 450 KN, and a rolling speed of 500 m / min.
[0129] The second pass has an entry thickness of 0.097 mm, an exit thickness of 0.066 mm, a reduction rate of 31.9%, a total entry tension of 3100 N, a total exit tension of 4100 N, a rolling force of 450 KN, and a rolling speed of 500 m / min.
[0130] The third pass has an entry thickness of 0.066 mm, an exit thickness of 0.045 mm, a reduction rate of 31.8%, a total entry tension of 2600 N, a total exit tension of 3200 N, a rolling force of 450 KN, and a rolling speed of 650 m / min.
[0131] The fourth pass has an entry thickness of 0.045 mm, an exit thickness of 0.032 mm, a reduction rate of 28.9%, a total entry tension of 1700 N, a total exit tension of 2100 N, a rolling force of 450 KN, and a rolling speed of 650 m / min.
[0132] The fifth pass has an entry thickness of 0.032 mm, an exit thickness of 0.023 mm, a reduction rate of 28.1%, a total entry tension of 1000 N, a total exit tension of 1200 N, a rolling force of 450 KN, and a rolling speed of 650 m / min.
[0133] The sixth pass has an entry thickness of 0.023 mm, an exit thickness of 0.018 mm, a reduction rate of 21.7%, a total entry tension of 800 N, a total exit tension of 950 N, a rolling force of 450 KN, and a rolling speed of 650 m / min. Finally, a rolled copper foil with a thickness of 0.018 mm is obtained.
[0134] (9) Cooling and drying: The electroplated copper foil is cooled and then dried to obtain the final rolled copper foil product.
[0135] The folding resistance test of the rolled copper foil product prepared in Example 1 was carried out:
[0136] The MIT folding fatigue test machine was used to conduct the MIT folding test, which used a weight of 500g, a bending radius of R=0.8mm, and a bending angle of 135°. After testing, the folding resistance of the rolled copper foil product was 267 times. It can be seen that compared with the rolled copper foil product obtained in Example 1, the folding resistance of the rolled copper foil prepared in Comparative Example 1 is significantly reduced.
[0137] Multiple exemplary embodiments of the present invention, however, without departing from the spirit and scope of the present invention, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the content disclosed in the present invention. Therefore, the scope of the present invention should be understood and identified as covering all these other variations or modifications.
Claims
1. A method for preparing a rolled copper foil, characterized in that: The following steps are involved: Smelting: Sn and P elements are added to the copper solution during the smelting process. After the smelting is completed, the Sn content in the solution is 0.10-0.12wt%, and the P content is 0.01-0.05wt%.
2. The method for preparing a rolled copper foil according to claim 1, characterized in that: In the smelting step, after the smelting is completed, the solution also contains the following components: Cu+Ag≥99.85wt%; S≤0.0015wt%; Fe≤0.001wt%; Zn≤0.0001wt%; Bi≤0.0001wt%; Sb≤0.0004wt%; Ni≤0.001wt%; Pb≤0.0005wt%; O≤0.0005wt%.
3. The method for preparing rolled copper foil according to claim 1, characterized in that: The content of Sn is 0.11-0.12 wt%; and / or The content of P is 0.031 to 0.05 wt%.
4. The method for preparing a rolled copper foil according to claim 1, characterized in that: After the smelting step, the method for preparing the rolled copper foil further comprises the following steps in sequence: casting, hot rolling, milling, rough rolling, intermediate rolling, finish rolling, and foil rolling.
5. The method for preparing rolled copper foil according to claim 4, characterized in that: In the casting step: a semi-continuous casting method is used, the casting temperature is controlled to be 900° C. to 1100° C., and the temperature is kept for 2 hours, and an ingot is obtained after the casting is completed.
6. The method for preparing rolled copper foil according to claim 4, characterized in that: In the hot rolling step: the starting rolling temperature is 850° C., the final rolling temperature is not less than 500° C., and after rolling for multiple passes, a slab with a thickness of 20 mm is obtained; and / or In the milling step: the slab obtained in the hot rolling step is subjected to milling treatment to obtain a slab with a thickness of 16.0 mm; and / or In the rough rolling step: the slab obtained in the milling step is rolled into a strip with a thickness of 1.0 mm in multiple passes; and / or In the intermediate rolling step: the strip obtained in the rough rolling step is annealed and then rolled into a strip with a thickness of 0.4 mm in two passes; and / or In the finishing rolling step: the strip obtained in the intermediate rolling step is subjected to continuous annealing treatment and then rolled into a copper plate strip with a thickness of 0.15 mm; and / or In the foil rolling step: the copper sheet strip obtained in the finish rolling step is subjected to foil rolling, which is divided into 5 to 7 rolling passes.
7. The method for preparing rolled copper foil according to claim 4, characterized in that: In the foil rolling step, there are 6 rolling passes as follows: First pass: entry thickness is 0.150mm, exit thickness is 0.097mm, reduction rate is 35.3%, total entry tension is 3500N, total exit tension is 5500N, rolling force is 450KN, and rolling speed is 500m / min; Second pass: the entry thickness is 0.097mm, the exit thickness is 0.066mm, the reduction rate is 31.9%, the total entry tension is 3100N, the total exit tension is 4100N, the rolling force is 450KN, and the rolling speed is 500m / min; The third pass: the entry thickness is 0.066mm, the exit thickness is 0.045mm, the reduction rate is 31.8%, the total entry tension is 2600N, the total exit tension is 3200N, the rolling force is 450KN, and the rolling speed is 650m / min; Fourth pass: the entry thickness is 0.045mm, the exit thickness is 0.032mm, the reduction rate is 28.9%, the total entry tension is 1700N, the total exit tension is 2100N, the rolling force is 450KN, and the rolling speed is 650m / min; The fifth pass: the entry thickness is 0.032mm, the exit thickness is 0.023mm, the reduction rate is 28.1%, the total entry tension is 1000N, the total exit tension is 1200N, the rolling force is 450KN, and the rolling speed is 650m / min; The sixth pass: the entry thickness is 0.023mm, the exit thickness is 0.018mm, the reduction rate is 21.7%, the total entry tension is 800N, the total exit tension is 950N, the rolling force is 450KN, the rolling speed is 650m / min, and finally a rolled copper foil with a thickness of 0.018mm is obtained.
8. The method for preparing rolled copper foil according to claim 4, characterized in that: After the foil rolling step, the method for preparing the rolled copper foil further comprises the following steps: Electroplating: The surface of the rolled copper foil is electroplated.
9. The method for preparing rolled copper foil according to claim 8, characterized in that: The electroplating step comprises: Roughening treatment: Cu in the roughening solution 2+ The ion concentration is 40g / L, the H2SO4 concentration is 120g / L, and the current density is 55A / dm 2 ; Curing treatment: Cu in the curing liquid 2+ The ion concentration is 50g / L, the H2SO4 concentration is 80g / L, and the current density is 45A / dm 2 ; Surface zinc plating treatment: ZnCl2 concentration in the plating solution is 50g / L, KCl concentration is 150g / L, boric acid concentration is 25g / L, the plating solution pH is 5, and the current density is 3A / dm 2 .
10. A rolled copper foil prepared by the method for preparing a rolled copper foil according to any one of claims 1 to 9.
Citation Information
Patent Citations
Rectangular rolled copper foil, flexible flat cable, rotating connector, and method for manufacturing rectangular rolled copper foil
CN107429324A
Sample preparation method for ductility detection of soft rolled copper foil
CN108225860A
Preparation method of rolled copper foil high in bending resistance
CN108246804A
Copper foil for flexible printed circuit, copper clad laminate using the same, flexible printed circuit, and electronic device
CN109385556A
Preparation method of rolled copper foil, rolled copper foil and application
CN117415162A